Critical evaluation and thermodynamic assessment of the MgO-V2O5 and CaO-V2O5 systems in air. (March 2017) - Cao, Zhanmin; Wang, Nai; Xie, Wei; Qiao, Zhiyu; Jung, In-Ho
Abstract: The MgO-V2 O5 and CaO-V2 O5 systems in air have been critically evaluated and thermodynamically assessed based on available experimental data. The liquid phase is described by the modified quasichemical model and all intermediate phases are treated as stoichiometric compounds. A set of self-consistent model parameters for all phases in both systems is obtained. The experimental phase equilibria and thermodynamic data in air are well reproduced within experimental error limits.